2005
DOI: 10.1615/critrevimmunol.v25.i6.20
|View full text |Cite
|
Sign up to set email alerts
|

The Phenotype and Function of Lung Dendritic Cells

Abstract: Dendritic cells (DCs) are central to the integration of innate and adaptive immunity. In contrast to B and T lymphocytes, DCs have retained many of the pattern recognition receptors and are thus uniquely able to sense stimuli such as tissue damage, necrosis, and bacterial and viral infection. Also, immature DCs respond to danger signals in the environment, which leads to their maturation, upon which DCs differentiate and acquire the ability to direct the development of the primary immune response. The ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
0
20
1
Order By: Relevance
“…However we have been able to show that there was a reduction in lymphocyte accumulation, a cell type shown to be pivotal for the development of allergic inflammation [35]. In contrast to our findings, a previous study has shown that melanocortin peptides did not suppress lymphocyte recruitment to the airways in female allergic balb/c mice despite, impairing eosinophil recruitment to the airways [19].…”
Section: Discussioncontrasting
confidence: 99%
“…However we have been able to show that there was a reduction in lymphocyte accumulation, a cell type shown to be pivotal for the development of allergic inflammation [35]. In contrast to our findings, a previous study has shown that melanocortin peptides did not suppress lymphocyte recruitment to the airways in female allergic balb/c mice despite, impairing eosinophil recruitment to the airways [19].…”
Section: Discussioncontrasting
confidence: 99%
“…DCs, widely distributed throughout the conducting airways and the peripheral lung, are derived from CD34 bone marrow progenitors (35). The lower overall number could thus be a reflection of the decreased recruitment of monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Highly specialized and notably heterogenous, DCs function as messengers and regulators between innate and acquired immunity (e.g. Reid, 1997;Hart, 1997;Banchereau and Steinman, 1998;Austyn, 1998;Satthaporn and Eremin, 2001;Dzionek et al, 2000;Webb et al, 2005;McKenna et al, 2005;Lommatzsch et al, 2007Lommatzsch et al, , 2010GeurtsvanKessel and Lambrecht, 2008;von Garnier and Nicod, 2009). Because DCs have the ability to induce a primary immune response in resting naïve T-lymphocytes and play a role in the maintenance of B-cell function and antigen memory (recall) responses (e.g.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…Because DCs have the ability to induce a primary immune response in resting naïve T-lymphocytes and play a role in the maintenance of B-cell function and antigen memory (recall) responses (e.g. Webb et al, 2005;Bessa et al, 2009), they were called 'professional antigen presenting cells' by, e.g., Lipscomb and Masten (2002) and Liu (2005). To better assess incoming antigens for possible threat, mature DCs particularly occur in tissues that interface between the external-and the internal environments and are therefore greatly exposed to microbial pathogens, harmful particulates, and injurious gases.…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%